Mycoplasma pneumoniae Among Children Hospitalized With Community-acquired Pneumonia - Kutty, Preeta K. (Clin Infect Dis, 2019)
BACKGROUND. The epidemiology of Mycoplasma pneumoniae (Mp) among US children (<18 years) hospitalized with community-acquired pneumonia (CAP) is poorly understood. METHODS. In the Etiology of Pneumonia in the Community study, we prospectively enrolled 2254 children hospitalized with radiographically confirmed pneumonia from January 2010-June 2012 and tested nasopharyngeal/oropharyngeal swabs for Mp using real-time polymerase chain reaction (PCR). Clinical and epidemiological features of Mp PCR–positive and –negative children were compared using logistic regression. Macrolide susceptibility was assessed by genotyping isolates. RESULTS. One hundred and eighty two (8%) children were Mp PCR-positive (median age, 7 years); 12% required intensive care and 26% had pleural effusion. No in-hospital deaths occurred. Macrolide resistance was found in 4% (6/169) isolates. Of 178 (98%) Mp PCR–positive children tested for copathogens, 50 (28%) had ≥1 copathogen detected. Variables significantly associated with higher odds of Mp detection included age (10–17 years: adjusted odds ratio [aOR], 10.7 [95% confidence interval CI, 5.4–21.1] and 5–9 years: aOR, 6.4 [95% CI, 3.4–12.1] vs 2–4 years), outpatient antibiotics ≤5 days preadmission (aOR, 2.3 [95% CI, 1.5–3.5]), and copathogen detection (aOR, 2.1 [95% CI, 1.3–3.3]). Clinical characteristics were non-specific. CONCLUSIONS. Usually considered as a mild respiratory infection, Mp was the most commonly detected bacteria among children aged ≥5 years hospitalized with CAP, one-quarter of whom had codetections. Although associated with clinically nonspecific symptoms, there was a need for intensive care in some cases. Mycoplasma pneumoniae should be included in the differential diagnosis for school-aged children hospitalized with CAP.